Fortification of soy sauce using various iron sources: Sensory acceptability and shelf stability - Ratana Watanapaisantrakul (2018)
Background. Soy sauces are available in different types and grades, which allows them to reach consumers of all socioeconomic groups. Ferric sodium ethylenediaminetetraacetic acid (NaFeEDTA) has been used for iron fortification of soy sauces in some countries, however, its high cost may make it unattractive to policymakers and industry. Objective. We ev aluated the feasibility of using more economical iron sources for iron fortification, with soy sauce of various types and grades used as a vehicle. Methods. Seven iron sources were tested for their feasibility for fortification of four types of soy sauce: naturally fermented in the traditional style, naturally fermented according to large-scale industrial formulas 1 and 5, and chemically hydrolyzed at 5 mg per serving (15 mL, per Thailand's food labeling regulations). Either citric acid or sodium citrate was added at 0.1% as a chelator. Results. Five iron sources - ferrous sulfate, NaFeEDTA, ferric ammonium citrate, ferrous lactate, and ferrous gluconate - did not significantly affect the sensory qualities of the product over a period of 3 months (p >.05). Ferrous fumarate and ferrous bisglycinate caused unacceptable precipitation. Less than 3% of 260 and 306 commonly cooked foods out of 871 and 772 preparations using soy sauces fortified with NaFeEDTA and ferrous sulfate, respectively, were found to be different from normal with regard to sensory qualities. The cost of fortification was US 0.22 cents to US 3.28 cents per bottle (700 mL). Conclusions. Both naturally fermented and chemically hydrolyzed soy sauces could be fortified with all five iron sources. Ferrous sulfate is the most appropriate source because of its low cost and acceptable sensory characteristics. Soy sauce is a promising vehicle for iron fortification, however, the bioavailability of iron in the products examined here needs to be evaluated under normal use conditions. © 2006, The United Nations University.